Assessment of the feed additive consisting of Saccharomyces cerevisiae CNCM I‐4407 (Actisaf® Sc 47) for rabbits for fattening and non‐food producing rabbits for the renewal of its authorisation (S. I. Lesaffre) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of a preparation of dried cells of Saccharomyces cerevisiae CNCM I‐4407 (Actisaf® Sc 47) as a zootechnical additive for rabbits for fattening and non‐food producing rabbits. The applicant provided evidence that the additive currently in the market complies with the existing terms of the authorisation. The Panel concluded that the additive remains safe for the target species, consumers and the environment. Regarding the safety for the user, the additive is not a skin or eye irritant. However, it should be considered as a potential skin and respiratory sensitiser, and any exposure through skin and respiratory tract is considered a risk. The present application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.